Cooperation Between Cancer and Fibroblasts in Vascular Mimicry and N2-Type Neutrophil Recruitment via Notch2–Jagged1 Interaction in Lung Cancer - Tsai, Ying-Ming; Wu, Kuan-Li; Liu, Yu-Wei; Chang, Wei-An; Huang, Yung-Chi; Chang, Chao-Yuan; Tsai, Pei-Hsun; Liao, Szi-Hui; Hung, Jen-Yu; Hsu, Ya-Ling (Frontiers in Oncology, 2021)
Background Angiogenesis is required for tumor development and metastasis, which is a major part in a pro-tumor microenvironment. Vascular mimicry (VM) is a process in which cancer cells, rather than endothelia, create an alternative perfusion system to support the tumor progression. Objectives To validate the role of VM and to develop a strategy to inhibit angiogenesis in lung cancer. Methods In this study, we utilized lung cancer samples to verify the existence of VM and conducted several experimental methods to elucidate the molecular pathways. Results H1299 and CL1-0 lung cancer cells were unable to form capillary-like structures. VM formation was induced by cancer-associated fibroblast (CAFs) in both in vitro and in vivo experiments. Notch2–Jagged1 cell–cell contact between cancer cells and CAFs contributes to the formation of VM networks, supported by Notch intracellular domain (NICD) 2 nuclear translocation and N2ICD target gene upregulated in lung cancer cells mixed with CAFs. The polarization of tumor-promoting N2-type neutrophil was increased by VM networks consisting of CAF and cancer cells. The intravasation of cancer cells and N2-type neutrophils were increased because of the loose junctions of VM. Disruption of cancer cell–CAF connections by a γ‐secretase inhibitor enforced the anticancer effect of anti‐vascular endothelial growth factor antibodies in a mouse model. Conclusion This study provides the first evidence that CAFs induce lung cancer to create vascular-like networks. These findings suggest a therapeutic opportunity for improving antiangiogenesis therapy in lung cancer.